2022
DOI: 10.3389/fpls.2022.861191
|View full text |Cite
|
Sign up to set email alerts
|

Genomics Enabled Breeding Strategies for Major Biotic Stresses in Pea (Pisum sativum L.)

Abstract: Pea (Pisum sativum L.) is one of the most important and productive cool season pulse crops grown throughout the world. Biotic stresses are the crucial constraints in harnessing the potential productivity of pea and warrant dedicated research and developmental efforts to utilize omics resources and advanced breeding techniques to assist rapid and timely development of high-yielding multiple stress-tolerant–resistant varieties. Recently, the pea researcher’s community has made notable achievements in conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 238 publications
(232 reference statements)
0
16
0
Order By: Relevance
“…Until now, at least seven fungal species have been identified as the causative agents of ascochyta blight of pea ( 2 , 3 , 5 7 ). They are soilborne, pathogenic fungi and survive as chlamydospores, mycelia, or sclerotia in soil, and they can coexist on peas or exist independently from each other ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, at least seven fungal species have been identified as the causative agents of ascochyta blight of pea ( 2 , 3 , 5 7 ). They are soilborne, pathogenic fungi and survive as chlamydospores, mycelia, or sclerotia in soil, and they can coexist on peas or exist independently from each other ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ascochyta blight (syn., black spot) is the most devastating disease of peas worldwide. Ascochyta blight reduces production, with yield losses of 28 to 88% depending on the environmental conditions and the quality of the peas ( 2 4 ). At least seven fungal species have been identified as pathogens of ascochyta blight of pea, including Ascochyta pisi , Ascochyta koolunga , Ascochyta pinodes , Ascochyta pinodella , Phoma herbarum , Phoma glomerata , and Boeremia exigua var.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotic stresses are crucial constraints to the productivity of crop plants, especially under climate change conditions (Parihar et al, 2022), and lead to more than 20% crop yield losses (Savignac et al, 2022). Galewski et al identified specific genomic features associated with seedling rhizoctonia resistance by whole genome sequencing of selected and unselected bulk derived from a synthetic outcrossing sugar beet population and the genome-wide variation resulting from the selection.…”
Section: Biotic Stress-relatedmentioning
confidence: 99%
“…Biotic stresses are crucial constraints to the productivity of crop plants, especially under climate change conditions ( Parihar et al., 2022 ), and lead to more than 20% crop yield losses ( Savignac et al., 2022 ). Galewski et al.…”
Section: Biotic Stress-relatedmentioning
confidence: 99%